To solve the quadratic equation \((x + 36)^2 - 38 = 251\), we first isolate the squared term.
-
Add 38 to both sides: \[ (x + 36)^2 = 251 + 38 \] \[ (x + 36)^2 = 289 \]
-
Take the square root of both sides: \[ x + 36 = \pm \sqrt{289} \] Since \(\sqrt{289} = 17\), we have: \[ x + 36 = 17 \quad \text{or} \quad x + 36 = -17 \]
-
Solve the two equations:
- For \(x + 36 = 17\): \[ x = 17 - 36 = -19 \]
- For \(x + 36 = -17\): \[ x = -17 - 36 = -53 \]
Thus, the solutions to the equation are: \[ x = -19 \quad \text{and} \quad x = -53 \]
The correct response is: \[ {-19, -53} \]